Character-Driven Strategies for Teaching the Indonesian Language in Islamic Higher Education - F, Fauziah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research is motivated by the status of the Indonesian Language subject as a General Compulsory University Course (MKWU) in Islamic higher education institutions, which therefore plays a strategic role in developing students’ literacy skills while strengthening Islamic character. The study aims to examine character education–based learning strategies for the Indonesian Language subject in Islamic Higher Education Institutions (PTAI). Using a library research method, this study identifies learning strategies that integrate Islamic and national character values into Indonesian language instruction. The results show that Indonesian language learning in PTAI is not only a means of enhancing academic language competence but also serves as a medium for the internalization of moral, religious, and national values. Effective learning strategies include the following steps: (1) developing comprehensive lesson planning, (2) designing character-based learning strategies in each learning stage, (3) preparing instructional materials, (4) selecting appropriate media, and (5) designing assessments, all of which apply character education principles inspired by relevant Islamic values. In conclusion, the implementation of character-based learning strategies in the Indonesian Language course at PTAI has the potential to produce graduates who are intelligent, virtuous, and possess strong Islamic character.